2009
DOI: 10.1166/jbn.2009.1045
|View full text |Cite
|
Sign up to set email alerts
|

Complement: Alive and Kicking Nanomedicines

Abstract: Administration of liposome- and polymer-based clinical nanomedicines, as well as many other proposed multifunctional nanoparticles, often triggers hypersensitivity reactions without the involvement of IgE. These anaphylactic reactions are believed to be secondary to activation of the complement system, giving rise to the release of anaphylatoxins C3a and C5a that initiate a wide array of responses through their effect on mast cells, polymorphonuclear cells, platelets and monocytes. Additionally, the terminal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 48 publications
0
53
0
Order By: Relevance
“…23,24 Here, we showed that IONPs provoked complement activation resulting in the generation of the anaphylatoxins C3a and C5a as well as the soluble terminal complement complex sC5b-9 in an ex vivo human whole blood model. Moreover, the IONPs induced the secretion of pro-inflammatory cytokines in whole blood from healthy donors.…”
Section: Discussionmentioning
confidence: 88%
“…23,24 Here, we showed that IONPs provoked complement activation resulting in the generation of the anaphylatoxins C3a and C5a as well as the soluble terminal complement complex sC5b-9 in an ex vivo human whole blood model. Moreover, the IONPs induced the secretion of pro-inflammatory cytokines in whole blood from healthy donors.…”
Section: Discussionmentioning
confidence: 88%
“…11,64,83 Mechanistically this is due to the generation of the terminal part of the complement pathway where the membrane attack complex is generated (C5b-9). This forms holes in biomembranes; in the case of bacteria this results in destruction of the cell by osmosis.…”
Section: Complement Activationmentioning
confidence: 99%
“…This makes its assembly and deposition on to the surface of a nanomaterial with high surface area (e.g. nanofibres, nanoparticles) rather difficult [6]. Furthermore, a surface-bound C3b is expected to occupy an area of 40 nm2 [7].…”
Section: Contact Angle Measurementsmentioning
confidence: 99%